STUDI EKSPLORASI DAN ANALISIS PENGARUH VIDEO GAME PADA KUALITAS PERTEMANAN: STUDI KASUS IT TAKES TWO - Kevin Anderson; Heru Wijayanto Aripradono (BETRIK, 2022)
It Takes Two is a game that is played in co-op with other players, this game can be played locally or online. Where each player controls one of the characters and works together to solve a problem such as passing obstacles and defeating enemies. In the It Takes Two game itself there are 9 chapters, namely Chapter 1: The Shed, Chapter 2: The Tree, Chapter 3: The Pillowfort, Chapter 4: Space Station, Chapter 5: Road to the Magic Castle, Chapter 6: Gates of Time, Chapter 7: Snowglobe, Chapter 8: Garden, Chapter 9: The Attic. This study aims to determine the effect of playing cooperative games on the quality of friendship. The method used in this research is the exploration and observation method. The results obtained in this study are that playing cooperative games has a positive influence on the quality of friendship at least temporarily because this study only takes 15 minutes, this is seen from observations by the author of the video recording with a duration of 15 minutes, namely the existence of mutual assistance between partners such as giving directions to partners, smiling at partners, and laughing at partners in playing the game.